2023
DOI: 10.3389/fimmu.2022.1084460
|View full text |Cite
|
Sign up to set email alerts
|

The role of major immune cells in myocardial infarction

Abstract: Myocardial infarction (MI) is a cardiovascular disease (CVD) with high morbidity and mortality worldwide, often leading to adverse cardiac remodeling and heart failure, which is a serious threat to human life and health. The immune system makes an important contribution to the maintenance of normal cardiac function. In the disease process of MI, necrotic cardiomyocytes release signals that activate nonspecific immunity and trigger the action of specific immunity. Complex immune cells play an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Infiltration of the ischemic site by immune cells can both promote cardiomyocyte death, inflammation, and subsequent post-MI remodeling and heart failure, as well as facilitate regeneration of damaged heart muscle at a later stage [90][91][92][93]. At the onset of MI, necrotic myocytes release damage-associated molecular patterns (DAMPs) and cytokines that activate the recruitment of non-specific immune cells such as monocytes, neutrophils, and dendritic cells from the peripheral vasculature into the infarcted area [94]. After the inflammatory phase, a specific immune response involving T and B lymphocyte infiltration initiates the repair of MI, in particular via the production of cytokines by regulatory T cells to promote macrophage polarization and myocardial healing [94].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltration of the ischemic site by immune cells can both promote cardiomyocyte death, inflammation, and subsequent post-MI remodeling and heart failure, as well as facilitate regeneration of damaged heart muscle at a later stage [90][91][92][93]. At the onset of MI, necrotic myocytes release damage-associated molecular patterns (DAMPs) and cytokines that activate the recruitment of non-specific immune cells such as monocytes, neutrophils, and dendritic cells from the peripheral vasculature into the infarcted area [94]. After the inflammatory phase, a specific immune response involving T and B lymphocyte infiltration initiates the repair of MI, in particular via the production of cytokines by regulatory T cells to promote macrophage polarization and myocardial healing [94].…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of MI, necrotic myocytes release damage-associated molecular patterns (DAMPs) and cytokines that activate the recruitment of non-specific immune cells such as monocytes, neutrophils, and dendritic cells from the peripheral vasculature into the infarcted area [94]. After the inflammatory phase, a specific immune response involving T and B lymphocyte infiltration initiates the repair of MI, in particular via the production of cytokines by regulatory T cells to promote macrophage polarization and myocardial healing [94]. Resolution of inflammation is achieved by macrophage recruitment in the injured site to polarize into anti-inflammatory macrophages that activate MI repair by secreting anti-inflammatory cytokines and eliminating necrotic cells [95].…”
Section: Discussionmentioning
confidence: 99%
“…CVDs are a group of diseases in which inflammation plays a role in the pathogenesis. Specifically, atherosclerosis and MI are associated with immune cell responses, including that of T cells [209,210]. Modulation of T cell activity occurs through the programmed death cell 1 pathway (PD-1/PD-L1), which is used in immunotherapy for the treatment of malignancies.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In addition to the innate immune system, the adaptive immune system also plays a role in the immune response after an MI [ 168 ]. Experimental studies showed that B cells are instrumental in orchestrating the inflammatory response after myocardial IRI, partially via mobilizing inflammatory monocytes to the infarct site [ 169 ].…”
Section: Ongoing Clinical Trials For Drugs Against Myocardial Iri: Po...mentioning
confidence: 99%